A historical sketch; life and time of Jonathan Hutchinson (1828-1913), the first sarcoidologist - Sharma, O.P.; Shigemitsu, H. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2008)
In the years preceding and following the turn of the 19th century several publications appeared independently that drew attention to what is now regarded as sarcoidosis. The first recorded and illustrated example is attributed to Jonathan Hutchinson of London. It appeared in Illustrations of Clinical Surgery (1877).